The Dynamics and Determinants of Slave Prices in an Urban Setting: Santiago de Chile, C. 1773-1822* - Llorca-Jana, M; Droller, F (Cambridge University Press, 2016)
This paper provides the first survey of slave prices for Santiago de Chile, c. 1773-1822. It also establishes the main determinants of slave prices during this period. We gathered and analysed over 3,800 sale operations. Our series confirm the usual inverted U-shape when prices are plotted against age, and that age was a very important determinant of slave prices. We also found that: female slaves were systematically priced over male slaves, quite contrary to what happened in most other markets; the prime age of Santiago slaves was 16-34, a younger range than for most other places; male slave prices moved in the same direction as real wages of unskilled workers; and the impact of the free womb law on market prices in 1811 was dramatic. © Instituto Figuerola, Universidad Carlos III de Madrid, 2016.